Melanoma: clinical, evolutive and histopathological characteristics of a series of 136 cases - Juliana Polizel Ocanha-Xavier; José Cândido Caldeira Xavier-Junior; Mariângela Esther Alencar Marques (Sociedade Brasileira de Dermatologia, 2018)
Abstract: BACKGROUND: The incidence of melanoma has been increasing in Brazil and all over the world. Despite improvements in diagnosis and treatment, mortality remains unchanged. OBJECTIVE: To associate clinical and histopathological aspects with the evolution of 136 cases of cutaneous melanoma. METHODS: Retrospective cohort study that analyzed all patients diagnosed with melanoma during the period from 2003 to 2011, with at least 4 years follow up. Archived slides were analyzed to study histopathological variables (Breslow, ulceration, mitoses and histological regression). Medical records were used to retrieve clinical variables (age, sex, localization, time of appearance, diameter) and progression (metastases or death). Association measures were assessed by statistical analysis. RESULTS: There was no statistically significant difference between groups according to age. Superficial spreading subtype showed lower Breslow (0.5mm) than acral lentiginous and nodular subtypes (2 and 4.6mm respectively), less ulceration and metastases (9.4% against 50 and 70.6%). Nodular subtype had higher mitoses' median (5.0/mm2) than superficial spreading and lentigo maligna (0.0/mm2, for both). Regression was more frequent in superficial spreading and lentigo maligna subtypes. There were only deaths by melanoma in the acral group, however, there were deaths for other reasons in groups superficial spreading one, acral lentiginous one and lentigo maligna two. STUDY LIMITATIONS: Use of medical records as a source of data to the study. CONCLUSIONS: Superficial spreading subtype presents better prognosis indicators. Histological subtype should be considered in follow-up and treatment protocols of patients with cutaneous melanoma.